2020
DOI: 10.1101/2020.03.25.007344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of Action of Autophagy Modulators Dissected by Quantitative Systems Pharmacology Analysis

Abstract: Autophagy plays an essential role in cell survival/death and functioning. Modulation of autophagy has been recognized as a promising therapeutic strategy against diseases/disorders associated with uncontrolled growth or accumulation of biomolecular aggregates, organelles or cells including those caused by cancer, aging, neurodegeneration, and liver diseases such as α1antitrypsin deficiency. Numerous pharmacological agents that enhance or suppress autophagy have been discovered. However, their molecular mechani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Furthermore, the glibenclamide group showed significant increase in H score of Beclin-1 when compared to the IRI group. To support this finding, Shi et al [25] reported that glibenclamide could modulate autophagy and suppress tubular cell apoptosis through downregulation of Beclin-1 gene transcription. Furthermore, the combined group obviously showed significant increase of H score of Beclin-1 when compared with the other groups, which may be attributed to the potent stimulatory effect of autophagy activity of both carvedilol and glibenclamide.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the glibenclamide group showed significant increase in H score of Beclin-1 when compared to the IRI group. To support this finding, Shi et al [25] reported that glibenclamide could modulate autophagy and suppress tubular cell apoptosis through downregulation of Beclin-1 gene transcription. Furthermore, the combined group obviously showed significant increase of H score of Beclin-1 when compared with the other groups, which may be attributed to the potent stimulatory effect of autophagy activity of both carvedilol and glibenclamide.…”
Section: Discussionmentioning
confidence: 92%